Modulated laser spot welding of dissimilar copper-aluminium connections. - Weigl, Markus; Schmidt, Michael (Proceedings of 4M/ICOMM conference 2009, 2009)
As a consequence of permanent rising demands on electronic devices the application of adapted materials gains in importance and leads to increasing challenges for the joining technologies. In this context the following article deals with laser micro-welding of copper-aluminium connections, whereas especially the influences of power modulations on mixing effects and formation of brittle phases in the welding zone are under examination. In contrast to spot welding without laser modulation actions, samples welded with frequencies less than 1 kHz and modulation factors up to 10% reach about 20% higher breaking resistances during tensile tests. These results are mainly caused by modified mixing scenes of both base materials during the molten state, which affects more favourable element dispersions and lower addictions for the formation of brittle fractures. Notably disadvantageous for the ductility of the connections are these brittle phases in case of conglomeration in the zones between the welding spot and the base materials. Since the mixing processes in these critical areas nearby the lines of fusion show no dependence on laser power modulations, no significant exertion of influence on the implied zones can be established up to now.<br
Keywords: modulated laser welding; dissimilar connections; copper; aluminium; brittle phases